Photomechanical crossroads - Comparing 19th-Century Chromocupography and Charles Eckstein’s method from a Printmaker’s Perspective. - Lopes, David; Machado, Graciela (Revelar: Revista de Estudos da Fotografia e Imagem, 2024)
Chromocupography is a photo-etching technique developed in 19th-century Portugal under the supervision of chemist José Júlio Rodrigues (1843-1923). Very scarce literature is associated with the process, and it doesn’t seem to have been widely used after being made public. At the time, the technique was presented as a variant of Charles Eckstein’s (1840-1913) method, working in Hague, Holland. Eckstein’s technique consisted of hatching the lithograph stone with very fine delicate multiple-point needles to produce tone variations. Chromocupography substitutes the stone for a copper plate and the needles for a special coating with resin, thus creating a granular reservation protecting the metal from the etching bath. With this paper, we aim to present how the technical entanglements which are felt from a practical experience of the contemporary printmaker. We will be showing the various results we obtained conducting research following the descriptions found in literature around the subject of Portuguese process chromocupography, at the Faculty of Fine Arts of the University of Porto within the project of Pure Print Archaeology (i2ADS/FBAUP).